Bitcoin on the Insurance Market - Kurek, Robert (Studia Oeconomica Posnaniensia, 2026)
From the perspective of the financial world the existence of cryptocurrency is no longer a novelty and decentralized virtual money is also entering the insurance market. The study presents the general characteristics of bitcoin and analyses certain theoretical scenarios of the presence of bitcoin itself in an insurance market, as well as the idea of an alternative money system with which it is related . The characteristics of potential bitcoin impact areas on the insurance market included in the study cover payments using BTC constituting the potential object of insurance, new risks related to the functioning of BTC and also operations performed by the insurance institutions based on BTC or taking advantage of the peer-to-peer idea associated with bitcoin.